Implementasi untuk Meningkatkan Keamanan Jaringan Menggunakan Deep Packet Inspection pada Software Defined Networks - Danaswara Prawira Harja; Andrian Rakhmatsyah; Muhammad Arief Nugroho (School of Computing, Telkom University, 2019)
AbstractToday, Software Defined Network (SDN) has been globally recognized as a new technology for network architecture. But, there is still lack in security. Many studies use methods such as the Intrusion Prevention System (IPS) and Intrusion Detection System (IDS) to deal with social problems. But there is still a lack of security in terms of network performance. To solve the problem, can be used Deep Packet Inspection method (DPII) which make administrators can directly know what happens to traffic in real time. In this research, DPI will be implemented as security method and tested with Denial of Service (DoS) attack with Direct Attack. The results of testing on SDN networks that have been added DPI can perform packet detection such as IDS and blocking such as IPS with good performance time in overcoming attack.Keywords: SDN, DPI, DoS attack, Direct Attack, performance